A review on experimental observation on structural performance of bamboo reinforced concrete beam - Solahuddin, Azuwa (Elsevier Ltd, 2024)
Bamboo has many usages. Incorporating bamboo enhances the reinforced concrete beam's (RCB) performance, properties and behaviour as internal reinforcement. A summary of how bamboo influences the RCB properties shall be studied. This review paper discusses the use of bamboo to reinforce RCB and briefly describes the topic. Previous experimental observation results showed that RCB constructed with bamboo significantly improved the flexural, stress-strain, load-deflection, failure mode, crack pattern, tensile, compression, and shear modulus of RCB. Since this bamboo has superior strength, force, mounting and anchoring properties, it can be used as an alternate interior reinforcement, replacing normal steel reinforcing bars in RCB. The structural behaviour and performance of RCB can be enhanced by utilising bamboo in civil and structural engineering, especially in building construction projects.